Entrepreneurship Development Communities based on Mosque: Educational Management Review - Tharaba, M. Fahim; Noviyanti, Shobihatul Fitroh (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to find a model of education management for the entrepreneurship development of community based on mosque as a form of community mental revolution movement. The research method used is participatory action research (PAR) which is carried out through four stages, namely, planning, observation, and reflection, which in its implementation are carried out in various cycles of activities with the people of Bantur District. The results showed that mosque-based community entrepreneurship development education management activities were able to identify the actual conditions of the community through a SWOT analysis, which in turn found strategies and methods in solving the problems they faced. After the planning is implemented, the community implements it with the assistance and facilitation of the researcher. Observations were made to identify and analyze strengths, weaknesses, challenges, and opportunities. This was done by involving the community. Furthermore, the community's efforts are then reflected and evaluated; both strengths, weaknesses, challenges, and opportunities are carried out by involving the community.